The Effect of Training Using Equipment on Some Skills And Motor Variables to Develop The Tactical Aspect of Youth Foot - Joudah, Jassim Majeed (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2025)
This study investigates the impact of systematically structured and scientifically grounded sports training program on the comprehensive development of youth football players. The research focuses on enhancing physical, technical, psychological, and cognitive competencies to optimize athletic performance. Given the role of youth athletes as a vital talent pipeline for professional clubs and national teams, the objective is to improve their performance levels through targeted training interventions. Materials and Methods. The study involved a sample of 34 youth players from Al-Karkh Football Club, all aged 19 years, representing their team in the Iraqi Premier League. An experimental research design was employed, dividing participants into two groups: an experimental group and a control group. The experimental group underwent a specialized training regimen developed by the researcher, while the control group continued with conventional training methods. The study assessed key technical skills— scoring, passing, and dribbling—as well as motor abilities, including agility, transitional speed, and motor response.  Results. The findings demonstrated that the experimental group, which engaged in the researcher-designed training program, exhibited significant improvements in both physical attributes and technical skills compared to the control group. These enhancements were evident in measures of skill execution and motor ability performance. Conclusion. The study concludes that the implementation of scientifically structured and purpose-driven training programs effectively enhances the physical and technical capabilities of youth football players. Such targeted interventions are recommended to develop young athletes who serve as essential contributors to the talent pool of professional football clubs and national teams.